A STUDY ON DYNAMIC RELATIONSHIP BETWEEN CRUDE OIL PRICES AND STOCK MARKET PRICES IN INDIA - Chinni, Dr. Naveen; .G.T, Ms. Amulya; Venkata Nooka Raju, Dr.Nagala Shyam (The journal of contemporary issues in business and government, 2022)
The Indian stock market is highly volatile. The effect of one market on another market is not new. However, the variations in the degree of impact and co-movement between the markets need to be examined. This research aims to study the dynamic relationship between Crude oil price and stock prices from April 2017 to March 2022. In order to establish the relationship between the exchange rate and the stock market price, ADF test is embarked to examine immovability of data and is evident that it is un-movable at initial difference level. The Johansen co-integration test of Johansen is applied to assess long-term balance of Nifty Index analysis with the Banking sector and to define the co-integration of the variables. Granger causality test is used to regulate causal & short-term relationship of the variables with the corresponding bidirectional of the causality among the variables.